2017
DOI: 10.1177/0340035217723355
|View full text |Cite
|
Sign up to set email alerts
|

First-year international graduate students’ transition to using a United States university library

Abstract: This article reports original research conducted at a US university exploring how incoming first-year international graduate students transition to a new academic environment, learn to conduct research, and utilize library resources and spaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…These results, however, are very similar to those of Cooper and Hughes (2017). While studying the use of library spaces by postgraduate students at the University of New Mexico, Cooper and Hughes (2017) found that 93 per cent of international postgraduate students expressed that they visit the library weekly or monthly. The possible reason for similarities between the findings of Cooper and Hughes and this study may be as a result of the strong contingent of postgraduate international students at the North-West University (2019).…”
Section: Library Visits By Postgraduate Studentssupporting
confidence: 71%
See 1 more Smart Citation
“…These results, however, are very similar to those of Cooper and Hughes (2017). While studying the use of library spaces by postgraduate students at the University of New Mexico, Cooper and Hughes (2017) found that 93 per cent of international postgraduate students expressed that they visit the library weekly or monthly. The possible reason for similarities between the findings of Cooper and Hughes and this study may be as a result of the strong contingent of postgraduate international students at the North-West University (2019).…”
Section: Library Visits By Postgraduate Studentssupporting
confidence: 71%
“…Similarly, only 42 per cent of postgraduate students claimed to visit the library at least once a week in Beard and Bawden (2012). These results, however, are very similar to those of Cooper and Hughes (2017). While studying the use of library spaces by postgraduate students at the University of New Mexico, Cooper and Hughes (2017) found that 93 per cent of international postgraduate students expressed that they visit the library weekly or monthly.…”
Section: Library Visits By Postgraduate Studentsmentioning
confidence: 75%
“…A handful of studies have investigated the information practice of international students who temporarily operate in another cultural context (e.g., Cooper & Hughes, 2017;Reyes et al, 2018;Zhao & Mawhinney, 2015). Some studies focused on international students' barriers, such as their different conceptions of research resources or challenges in developing IL skills due to cultural and linguistic differences (Ishimura & Bartlett, 2013;Zhao & Mawhinney, 2015).…”
Section: Multicultural Information Practicementioning
confidence: 99%
“…Most recently, a handful of studies have focused on the challenges that international students face in their transition to a new academic context (e.g. Cooper & Hughes, 2017;Hughes, Cooper, Flierl, Somerville & Chaudhary, 2018). However, the emphasis on the role of the academic library highlights the need for research that explores the processes of international student transition in more detail.…”
Section: Transitionmentioning
confidence: 99%